Cascading effects of climate variability on the breeding success of an edge population of an apex predator. Issue 11 (20th August 2020) - Gangoso, Laura; Viana, Duarte S.; Dokter, Adriaan M.; Shamoun‐Baranes, Judy; Figuerola, Jordi; Barbosa, Sergio A.; Bouten, Willem
Abstract: Large‐scale environmental forces can influence biodiversity at different levels of biological organization. Climate, in particular, is often associated with species distributions and diversity gradients. However, its mechanistic link to population dynamics is still poorly understood. Here, we unravelled the full mechanistic path by which a climatic driver, the Atlantic trade winds, determines the viability of a bird population. We monitored the breeding population of Eleonora's falcons in the Canary Islands for over a decade (2007–2017) and integrated different methods and data to reconstruct how the availability of their prey (migratory birds) is regulated by trade winds. We tracked foraging movements of breeding adults using GPS, monitored departure of migratory birds using weather radar and simulated their migration trajectories using an individual‐based, spatially explicit model. We demonstrate that regional easterly winds regulate the flux of migratory birds that is available to hunting falcons, determining food availability for their chicks and consequent breeding success. By reconstructing how migratory birds are pushed towards the Canary Islands by trade winds, we explain most of the variation (up to 86%) in annual productivity for over a decade. This study unequivocally illustrates how a climatic driver can influence local‐scale demographic processes while providing novel evidence of wind as a major determinant of population fitness in a top predator. Abstract : The authors demostrate how climate interacts with local demography to determine population fitness and viability. The mechanistic approach taken allowed us to unravel the cascading effects of the annual fluctuations of a major climatic phenomenon over the Atlantic on the vital rates of a wild bird population, and provided the first evidence of wind as a major determinant of a vertebrate's population fitness. Resumen: Los factores ambientales a gran escala afectan a la biodiversidad a distintos niveles de organización. El clima en particular, a menudo se asocia a la distribución de especies y gradientes de diversidad. Sin embargo, los mecanismos que lo vinculan con la dinámica de poblaciones siguen siendo poco conocidos. En este estudio revelamos el mecanismo a través del cual un factor climático, los vientos Alisios atlánticos, determinan la viabilidad de una población de una especie de ave rapaz. Monitorizamos la población canaria de Halcón de Eleonor durante una década (2007‐2017) e integramos distintos datos y métodos para reconstruir cómo la disponibilidad de alimento (pequeñas aves migratorias) es regulada por los vientos Alisios. Además, monitorizamos los movimientos de caza de adultos reproductores mediante GPS y el inicio de la migración de sus presas mediante un radar meteorológico, y simulamos la trayectoria de migración de estas presas utilizando un modelo espacialmente explícito basado en el individuo. Demostramos que los patrones de vientos del este regulan el flujo de aves migratorias que determina la disponibilidad de alimento para los halcones y sus pollos y, por tanto, su éxito reproductor. Al reconstruir cómo las aves migratorias son desviadas hasta las Islas Canarias por los vientos Alisios conseguimos explicar la mayor parte de la variación (hasta el 86%) en la productividad anual de los halcones durante una década. Este estudio ilustra cómo un fenómeno climático a gran escala puede afectar a los procesos demográficos a escala local y aporta nueva evidencia de que el viento puede ser un importante factor determinante de la eficacia biológica de un predador.